2000
DOI: 10.1046/j.1365-2893.2000.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis A and acquired immunity to hepatitis A virus in hepatitis B virus (HBV) carriers and in HBV‐ or hepatitis C virus‐related chronic liver diseases in Thailand

Abstract: A number of studies have suggested that the clinical course of hepatitis A virus (HAV) infection is more severe in patients with chronic liver disease (CLD). A study was undertaken to determine the impact of acute HAV in asymptomatic hepatitis B surface antigen (HBsAg) carriers (n = 20) and patients with hepatitis B virus (HBV)-(n = 8) or hepatitis C virus (HCV)-related (n = 4) CLD. Disease progression was compared with that in 100 patients with isolated HAV infection. No patient with HAV infection alone devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 3 publications
0
28
1
1
Order By: Relevance
“…It has been reported that when hepatitis A is superimposed on chronic hepatitis C, it frequently shows critical clinical course and accompany high rate of fulminant hepatitis and mortality 10. However, the affect of hepatitis B virus (HBV) infection on the severity of viral hepatitis A differs among researches 10,14-17…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that when hepatitis A is superimposed on chronic hepatitis C, it frequently shows critical clinical course and accompany high rate of fulminant hepatitis and mortality 10. However, the affect of hepatitis B virus (HBV) infection on the severity of viral hepatitis A differs among researches 10,14-17…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of a severe clinical course has, however, been suggested by some reports from Asia. For example, in a study from Thailand, 29% of patients with HAV superinfection died, and all of them were older than 50 (2 of the 3 superinfected patients in the present study were in this age group) [22,23]. Authors from South Korea found a 22-fold increase in the risk of fulminant hepatitis in hepatitis A superimposed on HBsAg carriage; in their analysis, this clinical scenario was observed in 12% of the cases [24].…”
Section: Discussionmentioning
confidence: 42%
“…In recent years, two studies have investigated the influence of acute HAV superinfection in Taiwan and Thailand, areas with endemic HAV and HBV infection. Chu and Liaw15 reported that HBsAg carriers were at a nine-fold increased risk of fulminant hepatitis compared with non-carriers, and Pramoolsinsap17 reported that fulminant or submassive hepatitis occurred in 10 of 20 (55%) HBsAg carriers and in 4 of 12 (33%) patients with HBV- or HCVrelated chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%